Book Review - Sherry, Arthur H. (1975)
A book review of Criminal Procedure by Abraham S. Goldstein and Leonard Orland, and Cases and Comments on Criminal Procedure by Fred E. Inbau, James R. Thompson, James B. Haddad, James B. Zagel and Gary L. Starkman, Modern Criminal Procedure, 4ht Ed by Yale Kamisar, Wayne R. LaFave, and Jerold H. Israel, The Process of Criminal Justice: Investigation by H. Richard Uviller, Criminal Process, 2nd Ed by Lloyd L. Weinre